Macrooxazoles A–D, New 2,5-Disubstituted Oxazole-4-Carboxylic Acid Derivatives from the Plant Pathogenic Fungus Phoma macrostoma - Blondelle Matio Kemkuignou; Laura Treiber; Haoxuan Zeng; Hedda Schrey; Rainer Schobert; Marc Stadler (Molecules, 2020)
In our ongoing search for new bioactive fungal metabolites, four previously undescribed oxazole carboxylic acid derivatives (1–4) for which we proposed the trivial names macrooxazoles A–D together with two known tetramic acids (5–6) were isolated from the plant pathogenic fungus Phoma macrostoma. Their structures were elucidated based on high-resolution mass spectrometry (HR-MS) and nuclear magnetic resonance (NMR) spectroscopy. The hitherto unclear structure of macrocidin Z (6) was also confirmed by its first total synthesis. The isolated compounds were evaluated for their antimicrobial activities against a panel of bacteria and fungi. Cytotoxic and anti-biofilm activities of the isolates are also reported herein. The new compound 3 exhibited weak-to-moderate antimicrobial activity as well as the known macrocidins 5 and 6. Only the mixture of compounds 2 and 4 (ratio 1:2) showed weak cytotoxic activity against the tested cancer cell lines with an IC50 of 23 µg/mL. Moreover, the new compounds 2 and 3, as well as the known compounds 5 and 6, interfered with the biofilm formation of Staphylococcus aureus, inhibiting 65%, 75%, 79%, and 76% of biofilm at 250 µg/mL, respectively. Compounds 5 and 6 also exhibited moderate activity against S. aureus preformed biofilm with the highest inhibition percentage of 75% and 73% at 250 µg/mL, respectively.